PENERAPAN TEKNIK MONTAGE EDITING DALAM PEMBUATAN VIDEO COMPANY PROFILE SEKRETARIAT DAERAH KOTA BOGOR - Nuranijiwa, Nadila; Rahmawati, Alfi; Kuntoro, Diadji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the suboptimal delivery of institutional information by the Regional Secretariat of Bogor City, particularly in utilizing engaging and communicative audiovisual media in the digital era. This study aims to analyze the editing process of a company profile video, examine the application of montage editing techniques based on Eisenstein’s theory, and evaluate its effectiveness through Instagram Reels. The study employs a practice-based approach with a project-based method, carried out collaboratively by a production team through systematic stages with continuous evaluation. The results show that montage editing is able to create a dynamic visual flow, clarify narrative structure, and enhance information delivery through integrated visual and audio elements. Furthermore, distribution via Instagram Reels increases audience reach and user engagement. In conclusion, montage editing proves effective in delivering concise, engaging, and easily understood institutional information while strengthening the organization’s image in digital media.